Kdo zmore in si zna privoščiti zdravje? - Starc, Gregor (Šport (Ljubljana), 2010)
The questionnaire Slovenian Public Opinion enables us to roughly analyse the patterns of sport-recreational practices of people and to identify some a motivational factors that turn people away from sport-recreational exercising. The regression model, built upon some selected variables showed, that the Slovenian Public Opinion questionnaire enables precise identification of people who are involved in sport-recreational activities but is much less precise in identification of sedentary individuals. The analysis showed that leisure-time sporting activities of people are influenced mostly by age, education, health and satisfaction with monthly income. On the other hand, gender, actual monthly income, type of residential environment, physical status, quantity of available leisure time and time, allocated for television watching, do not have statistically important predictive power. According to the established criteria of physical activity only 46 percent of Slovenian citizens reach the threshold of physical activity which enables the improvement of physical health and fitness.
Keywords: motivacija; odrasli; prihodki; raziskave; rekreacija; Slovenija; šport; športna aktivnost